Pengaruh Penggunaan Media Animasi berbasis YouTube terhadap Hasil Belajar Kognitif Peserta Didik pada Materi Virus Kelas X SMA - Khairunnisa Laselvy; Rahmawati D (MASALIQ, 2025)
The advancement of information and communication technology offers significant opportunities to enhance learning quality, particularly in biology, a subject often perceived by students as abstract and difficult to comprehend. This study aims to examine the effect of using YouTube-based animation media on the cognitive learning outcomes of Grade X senior high school students in the topic of viruses. The research employed an experimental method with a Posttest Only Control Design, involving 67 students from SMA Negeri 2 Batusangkar in the 2025/2026 academic year. Participants were divided into two groups: an experimental class using YouTube-based animation media and a control class using PowerPoint media. Data were collected through a validated multiple-choice test consisting of 20 items. Data analysis was conducted using normality, homogeneity, and t-tests via SPSS version 20. The results showed that the data were normally distributed and homogeneous, and there was a significant difference between the learning outcomes of the experimental and control classes (significance value 0.019 < 0.050). The average posttest score of the experimental class was 79.19, higher than the control class score of 71. These findings indicate that the use of YouTube-based animation media positively affects students’ cognitive learning outcomes. The study concludes that integrating innovative digital media into biology instruction is essential and offers practical contributions for teachers in designing effective and engaging learning strategies.